The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nano11030606
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Effects of Inhaled Nanoparticles in Cell Culture Models for Prolonged Exposure

Abstract: Respiratory exposure of humans to environmental and therapeutic nanoparticles repeatedly occurs at relatively low concentrations. To identify adverse effects of particle accumulation under realistic conditions, monocultures of Calu-3 and A549 cells and co-cultures of A549 and THP-1 macrophages in the air–liquid interphase culture were exposed repeatedly to 2 µg/cm2 20 nm and 200 nm polystyrene particles with different functionalization. Particle accumulation, transepithelial electrical resistance, dextran (3–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…In tricultures, no effect of NM-300K was seen on DNA damage in EA.hy926 cells. This might be linked to the potential uptake of NMs by the dTHP-1 cells as previously shown [ 75 , 81 ] making the material less available for cell exposure. One can even speculate if the exposed THP1 cells trigger an inflammatory reaction that can promote DNA repair [ 82 ].…”
Section: Discussionmentioning
confidence: 95%
“…In tricultures, no effect of NM-300K was seen on DNA damage in EA.hy926 cells. This might be linked to the potential uptake of NMs by the dTHP-1 cells as previously shown [ 75 , 81 ] making the material less available for cell exposure. One can even speculate if the exposed THP1 cells trigger an inflammatory reaction that can promote DNA repair [ 82 ].…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that such a collaboration mechanism could involve NLRP3 inflammasome [ 21 , 65 ] or activation of pro-inflammatory transcription factors [ 65 ]. In the literature, other studies using lung co-culture models reported significant pro-inflammatory effects of SiO 2 [ 21 , 22 ], TiO 2 [ 21 , 43 ], CeO 2 [ 43 ], quartz [ 52 ], PLGA [ 24 ], polystyrene [ 67 ], and CuO [ 65 ] NPs. However, most of these studies either did not compare the inflammatory response measured in co-culture with mono-culture models or compared it only with epithelial cells and not with macrophages [ 43 , 52 , 65 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, other studies using lung co-culture models reported significant pro-inflammatory effects of SiO 2 [ 21 , 22 ], TiO 2 [ 21 , 43 ], CeO 2 [ 43 ], quartz [ 52 ], PLGA [ 24 ], polystyrene [ 67 ], and CuO [ 65 ] NPs. However, most of these studies either did not compare the inflammatory response measured in co-culture with mono-culture models or compared it only with epithelial cells and not with macrophages [ 43 , 52 , 65 , 67 ]. Among these studies, only Dekali et al have actually demonstrated an increased inflammatory response in co-culture compared to epithelial cells and macrophages in mono-culture as we have [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Basic ALI airway models, consisting of respiratory cells only, are stable for prolonged times. If, however, immune cells are included, particularly when cell lines are used, the model becomes unstable [69]. This is due to the fact that cell types have different requirements for survival and growth.…”
Section: In Vitro Models For the Healthy Lungmentioning
confidence: 99%